Houseboat, Yellowknife Bay -- photograph ... - Seale, Linda N. (University of Alberta Library, 2012)
Houseboat frozen into the ice on Yellowknife Bay, Northwest Territories. The ice is thick enough to support vehicles. Access is by boat in summer, and may be limited during breakup and freeze-up. Jolliffe Island in the background. Photograph taken March 10, 2012 ...